Which factor explains the life‐history of Xanthium strumarium L., an aggressive alien invasive plant species, along its altitudinal gradient?. (9th January 2022) - Ullah, Rafi; Khan, Nasrullah; Ali, Kishwar
Abstract: Invasive biology acknowledges the concept of better performance by invasive plants in the introduced range. Xanthium strumarium L. is one of the successful invasive species in Khyber Pakhtunkhwa, Pakistan. The phenological pattern, vegetative and reproductive traits plasticity analysis of the species was explored to explain the invasive success across the altitudinal gradient in the current invaded habitats. Phenological patterns and timing (seedling, vegetative growth, flowering and fruiting, drying, and seed bank) were observed during a full year for two seasons. We also examine plant functional traits at altitudes of 500, 1000, and 1500 m a.s.l. to assess traits and biomass variations. The X. strumarium exhibits late vegetative and reproductive phenology at higher altitudes, enabling them to occupy an empty niche and benefit from decreased competition for resource acquisition. The lower altitude plants show a higher growth rate (stem size increase, number of leaves, and leaf area) due to the higher nutrient availability. Higher altitude plants have the highest reproductive biomass and biomass ratio revealing plant abilities to be reproductively adapted in the higher altitudes. Among climatic variables, mean yearly temperature, mean annual yearly humidity, and mean day length in hours, while in soil variables, organic matter and nitrogen percentage significantly affect the phenological and morphological stages. Therefore, we conclude that X. strumarium can invade higher altitudes with a shift in its phenological and morphological changes making the invasion process successful.